METAPHORIC PERCEPTIONS OF SOCIAL STUDIES TEACHER CANDIDATES ON THE HOMELAND CONCEPT - Sagdic, Mustafa; Ilhan, Genc Osman (MARMARA UNIV, 2018)
The purpose of the present study is to reveal social sciences teacher candidates perceptions on the concept of homeland by means of the metaphors they use. The study was participated by 100 volunteer teacher candidates teaching within the 2017-2018 academic year in Social Sciences Education, Faculty of Education, Yildiz Technical University in Istanbul. Answers to the following questions were sought in the study: (1) How do teacher candidates conceptualize their percetions of the concept homeland? (2) How do demographic features of teacher candidates affect their perceptions of homeland? The data of the study were obtained by having the participating social sciences teacher candidates fill in the sentence Homeland is like ..., because.... Phenomenological design was used in the study and the obtained data were analyzed with content analysis. As a result of the research, the candidates of Social Studies Teachers have submitted a total of 51 valid metaphors regarding the concept of Homeland. These metaphors are grouped into 4 different conceptual categories by their common characteristics. The Social Studies Teacher Candidates who participated in the survey perceived the homeland 47% as a vital necessity, 28% as an emotional space, 17% as a place with a sacred value, and 8% as a place combining the differences.
Keywords: Social Studies Education; Metaphor; Teacher Candidate; Homeland; PATRIOTISM; Geography